2019
DOI: 10.1021/acsanm.9b00862
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Boron Nitride Membranes for Helium Separation

Abstract: Porous boron nitride (BN) membranes PBN-BH, PBN-BNH, and PBN-NH were designed as promising membranes for purifying He from natural gas by using density functional theory. The three BN membranes were precisely regulated to form suitable pore sizes with high stability for He separation. The PBN-BH membrane exhibited ultrahigh selectivities of He over Ne, Ar, N2, CO2, and CH4, which were approximately 106–1066 times larger than those of the two other structures. Among the three membranes, PBN-BH exhibited the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…44 As listed in Table 1, the cohesive energies of the PC 2 , PC 3 , PC 5 , and PC 6 monolayers are −6.07, −6.38, −6.85, and −6.94 eV per atom, respectively, which agree well with previous results, 29 further confirming the reliability of our calculation parameters. Moreover, it can be clearly found that the PC x monolayer becomes more stable with the increasing carbon content, and all of the cohesive energies are smaller than those of black phosphorus (−3.43 eV per atom) 45 as well as nanoporous boron nitride (−5.39 to −4.90 eV per atom), 46 suggesting that these PC x monolayers hold great promise for experimental synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…44 As listed in Table 1, the cohesive energies of the PC 2 , PC 3 , PC 5 , and PC 6 monolayers are −6.07, −6.38, −6.85, and −6.94 eV per atom, respectively, which agree well with previous results, 29 further confirming the reliability of our calculation parameters. Moreover, it can be clearly found that the PC x monolayer becomes more stable with the increasing carbon content, and all of the cohesive energies are smaller than those of black phosphorus (−3.43 eV per atom) 45 as well as nanoporous boron nitride (−5.39 to −4.90 eV per atom), 46 suggesting that these PC x monolayers hold great promise for experimental synthesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Permeance is an indispensable indicator to determine the displacement efficiency of N 2 over water/salt [ 3 ]. Table 1 shows the permeances of N 2 passing through SiO 2 with five interlayer structures with different porosities.…”
Section: Discussionmentioning
confidence: 99%
“…Oil has aroused growing attention as a crucial energy resource around the world [ 1 , 2 , 3 ]. Oilfield exploration technology is vigorously investigated to discover more oil resources [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translocation Energy Barrier. The energy barrier (Δ) for gas flow through a given pore can be calculated using 61…”
Section: ■ Methodsmentioning
confidence: 99%